KEKERASAN DISKURSIF ATAS NAMA “WAR ON TERRORISM” : BENTUK BARU PELANGGARAN HAM - Muhammad Zuhdan (Universitas Sultan Ageng Tirtayasa, 2016)
Abstract: This paper is about to see the discourse of the war on terrorism by using Foucaldian perspective. The thesis said that the discourse of